The role of dermoscopy and digital dermoscopy follow-up in the clinical diagnosis of melanoma: clinical and dermoscopic features of 99 consecutive primary melanomas - Gabriel Salerni; Teresita Terán; Carlos Alonso; Ramón Fernández-Bussy (Mattioli1885, 2014)
Background: Early recognition is the most important intervention to improve melanoma prognosis. Objective: To report the value of dermoscopy and digital dermoscopy in the clinical diagnosis of malignant melanoma (MM). Methods: Retrospective analysis of 99 consecutive primary MMs diagnosed between 2010 and 2013. The MMs were divided into 3 groups: 1) the MM was the reason for consultation (MMC), 2) the MM was detected during routine control of nevi (MMRC), and 3) the MM was detected due to changes observed during digital dermoscopy follow-up (MMDFU). Clinical, dermoscopic and histologic features were assessed. Results: A total of 99 MMs were diagnosed in 89 patients (55% male) with a mean age of 50.8 (18-93) years. Of all the MMs, 35 were the reason for patient consultation (MMC), 52 were detected during routine control of nevi (MMRC) and 12 were diagnosed due to changes observed with digital dermoscopy (MMDFU). On clinical examination, 74.2 % of MMC met the 4 ABCD criteria, while only 30.7 % of MMRC and 8.3 % of MMDFU. Most MMC were correctly classified as malignant according to dermoscopy, but 44.2% of MMRC and only 16.7% of MMDFU. 22.9% of MMC, 50% of MMRC and 58.3% of MMDFU were in situ. Mean Breslow thickness was significantly lower in the MMDFU group (0.52 mm) than in the MMRC and MMDFU groups (0.77 and 1.43 mm respectively). Conclusions: The use of dermoscopy and digital dermoscopy allows the detection of MMs in early stages, even in the absence of specific criteria for malignancy.